Amaranthaceae (Caryophyllales) richness and distribution in the state of Aguascalientes, Mexico - Manuel Higinio Sandoval Ortega; María Elena Siqueiros-Delgado; Joaquín Sosa-Ramírez; Rosa Cerros-Tlatilpa (Botan‪ical Sciences, 2017)
Background: The Amaranthaceae family has a cosmopolitan geographic distribution, with 174 genera and about 2050 to 2500 species is the most diverse family within the order Caryophyllales, and includes about 50 % of species of eudicotiledóneas with C4 photosynthesis. Its species live mainly in arid environments, saline habitats and areas of disturbance, many are common weeds.